Photovoltaic power generation spatial planning and carbon emission reduction benefit assessment based on integrated model: a case study of Qinghai province - He, Junjie; Wang, Simin; Zhong, Boyang; Zhang, Qianrong (Frontiers in Environmental Science, 2025)
As an important source of clean energy, the Photovoltaic (PV) industry still requires in-depth research to optimize its development space and maximize carbon emission reduction benefits. This study takes Qinghai Province as the research area, integrating topographical, climatic, and economic factors to establish a Photovoltaic suitability evaluation system encompassing 15 indicators. Subsequently, the spatial distribution of feasible development zones was assessed, taking into account various constraints. Then, the binary local Moran’s I index method was used to analyze its spatial coupling relationship with electricity consumption. Finally, the benefits of carbon emission reductions were quantified. The results indicate that approximately 52.61% of Qinghai Province is considered to be an area with development potential, with a spatial distribution characterized by three belts and two areas. Meanwhile, there is a significant correlation between Photovoltaic power generation potential and electricity demand. It is predicted that by 2030, Qinghai Province’s electricity consumption will reach 1.235 × 1012 kwh. To achieve a balance between supply and demand, it will be necessary to construct approximately 18,849.35 km2 of Photovoltaic power generation facilities, which are expected to reduce carbon dioxide emissions by 9.48 × 108t annually. This study provides scientific basis for the optimized development of the Photovoltaic industry, helping to achieve regional energy transition and carbon emission reduction targets, and promoting sustainable development.